Association of tumor necrosis factor‐α inhibitors and liver cirrhosis in patients with rheumatoid arthritis: A nationwide population‐based nested case‐control study. (7th January 2022) - Chen, Der‐Yuan; Lin, Ching‐Heng; Chen, Hsin‐Hua; Tang, Kuo‐Tung
Abstract: Aim: Results from various studies are controversial regarding long‐term hepatic effects of tumor necrosis factor (TNF)‐α inhibitors. Here we aimed to investigate the development of liver cirrhosis with TNF‐α inhibitors use in patients with rheumatoid arthritis (RA). Method: This nested case‐control study was based on the National Health Insurance Research Database (January 1, 2000 to December 31, 2008) of Taiwan. We identified 559 adult RA patients who developed liver cirrhosis, and 1055 matched control RA patients. TNF‐α inhibitors of interest in the study period included adalimumab and etanercept. Multivariate logistic regression analysis for the development of liver cirrhosis with respect to use of TNF‐α inhibitors was performed. Results: The incidence rate of liver cirrhosis was 274 per 100 000 person‐years in newly diagnosed RA patients. We found the use of TNF‐α inhibitors was not associated with the development of liver cirrhosis in RA patients (odds ratio 1.02, 95% confidence interval 0.61, 1.70) after adjustment for potential confounders. In addition, the finding was robust to an unobserved confounder. Conclusion: We found no association between the use of TNF‐α inhibitors and development of liver cirrhosis in RA patients.